Genome Assembly of the Canadian two-row Malting Barley cultivar AAC Synergy - Wayne Xu; James R Tucker; Wubishet A Bekele; Frank M You; Yong-Bi Fu; Raja Khanal; Zhen Yao; Jaswinder Singh; Brian Boyle; Aaron D Beattie; François Belzile; Martin Mascher; et al. (G3: Genes, Genomes, Genetics, 2021)
AbstractBarley (Hordeum vulgare